Let $X_i$ be iid exponential random variables. I want to calculate $Var\left(\sqrt{\bar{X}/6}\right).$

The idea I had to simplify this is expressing it as $$Var\left(\sqrt{\frac{\bar{X}}{6}}\right) = E\left(\frac{\bar{X}}{6}\right) - \left[E\left(\sqrt{\frac{\bar{X}}{6}}\right)\right]^2.$$

This still leaves me with the problem of solving $E(\sqrt{\bar{X}/6})$. How do I deal with the square root inside the expectation?

  • 3
    $\begingroup$ It is not going to be a real number because a normal random variable takes on negative values. $\endgroup$ Apr 2, 2017 at 1:08
  • $\begingroup$ @user3903581 Thank you, let me amend the question to make it more practical $\endgroup$
    – kingledion
    Apr 2, 2017 at 1:09
  • $\begingroup$ Is the sample size $n$ or 6? Anyway, you may be able to use the fact that the sum of Exponentials is a Gamma distribution ... $\endgroup$
    – wolfies
    Apr 2, 2017 at 6:30

3 Answers 3


The sample mean from an exponential($\lambda$) sample is gamma($n$, $\lambda/n$) distributed.

It's a fact that the square root of $\overline{X}$ therefore has a generalized gamma distribution with parameters $p=2$, $d=2n$, and $a = \sqrt{\lambda/n}$, so it's mean is

$$ a \frac{ \Gamma( (d+1)/p )}{\Gamma(d/p)} = \sqrt{\lambda/n} \cdot \frac{ \Gamma( (2n+1)/2)}{ \Gamma(n)}$$

Divide this by $\sqrt{6}$ and there's your answer.

  • 1
    $\begingroup$ Is $\lambda$ standing for a scale parameter in your formulation? $\endgroup$ Apr 2, 2017 at 14:03
  • $\begingroup$ Yes. If $\lambda$ is supposed to be the rate, replace $\lambda$ with $1/\lambda$ in the final answer. $\endgroup$
    – gammer
    Apr 2, 2017 at 14:44

Say the parameter to each distribution is $\lambda$. First, $$ E\left[\frac{\bar{X}}{6}\right] = [6\lambda]^{-1} $$ by linearity. Then, because $Y = \sum_i X_i \sim \text{Gamma}(n,1/\lambda)$ \begin{align*} E\left(\sqrt{\frac{\bar{X}}{6}}\right)&= \int \sqrt{\frac{y}{6n}} \frac{\lambda^n }{\Gamma(n)}y^{n-1}e^{-y\lambda} dy \\ &= (6n)^{-1/2}\frac{\lambda^n}{(n-1)!} \int y^{n + 1/2 - 1}e^{-y\lambda}dy \\ &= (6n)^{-1/2}\frac{\lambda^n}{(n-1)!} \left[\frac{\Gamma(n+1/2) \lambda^{-(n+1/2)} }{\Gamma(n+1/2)\lambda^{-(n+1/2)}}\right] \int y^{n + 1/2 }e^{-y\lambda}dy \\ &= (6n)^{-1/2}\frac{\lambda^n}{(n-1)!} \Gamma(n+1/2) \lambda^{-(n+1/2-1)} \\ &= (6n)^{-1/2} \lambda^{1/2} \frac{\Gamma(n+1/2) }{\Gamma(n) } \end{align*}


The Exponential distribution is a special case of a Gamma ($G$) distribution. If $X \sim \text{Exp}(\lambda)$ where $\lambda$ is the rate parameter (so ($E(X) = 1/\lambda)$, then (shape -scale parametrization)

$$ \sum_{i=1}^n X_i \sim G(n, 1/\lambda) \implies \bar X = \frac 1n \sum_{i=1}^n X_i \sim G(n, 1/n\lambda) $$

Now, $$Z = \sqrt {\bar X} \implies \bar X = Z^2 \implies \frac {\partial \bar X}{\partial Z} = 2Z$$

Then by the change-of-variable formula we have that the density of $Z$ is

$$f_Z(z) = \left |\frac {\partial \bar X}{\partial Z}\right| \cdot f_{\bar X}(z)$$

$$\implies f_Z(z) = \frac {2z}{\Gamma(n)\cdot (1/n\lambda)^n}\cdot (z^2)^{n-1} \cdot\exp \{- z^2/(1/n\lambda)\} $$

$$\implies f_Z(z) = \frac {2}{\Gamma(n)\cdot (1/n\lambda)^n}\cdot z^{2n-1} \cdot\exp \{- z^2/(1/n\lambda)\}$$

Set $p\equiv 2,\;\; n \equiv d/p \equiv d/2,\;\; a\equiv (1/n\lambda)^{1/2}$. Then we can write

$$f_Z(z) = \frac {p}{\Gamma(d/p)\cdot a^d}\cdot z^{d-1} \cdot\exp \{- z^2/a^2\}$$

This is the density of the Generalized Gamma distribution, and so we have

$$E(Z) = E\left[\sqrt{\bar X}\right] = a\frac {\Gamma[(d+1)/p]}{\Gamma(d/p)}$$

and reverting back to the original parameters we obtain

$$E\left[\sqrt{\bar X}\right] = \frac{1}{\sqrt{n\lambda}}\cdot \frac {\Gamma[n+(1/2)]}{\Gamma(n)}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge that you have read and understand our privacy policy and code of conduct.

Not the answer you're looking for? Browse other questions tagged or ask your own question.